Nanocoatings size effect in nanostructured films - Aliofkhazraei, Mahmood; SpringerLink (Online service). (Berlin New York Springer, 2011)
ize effect in structures has been taken into consideration over the last years. In comparison with coatings with micrometer-ranged thickness, nanostructured coatings usually enjoy better and appropriate properties, such as strength and resistance. These coatings enjoy unique magnetic properties and are used with the aim of producing surfaces resistant against erosion, lubricant system, cutting tools, manufacturing hardened sporadic alloys, being resistant against oxidation and corrosion.   This book reviews researches on fabrication and classification of nanostructured coatings with focus on size effect in nanometric scale. Size effect on electrochemical, mechanical and physical properties of nanocoatings are presented.
Preface -- Synthesis, processing and application of nanostructured coatings.- Size dependency in nanostructures.-   Characterization of nanostructured coatings -- Size effect in electrochemical properties of nanostructured coatings -- Size effect in mechanical properties of nanostructured coatings -- Size effect in physical and other properties of nanostructured coatings -- Conclusions -- Index.
Electronic reproduction.
Keywords: Coatings; Nanostructured materials; Electronic books